(Neo)Liberal Scripts: Settler Colonialism and the British Columbia School Curriculum - Lamb, Christopher (2015)
Thesis (Master, Geography) -- Queen's University, 2015-10-08 12:11:37.135 This thesis explores the challenges to decolonizing education in British Columbia (BC), one of the thirteen provinces and territories in Canada. It is an analysis of the K-12 curriculum documents in BC. The analysis is based on critical literature on settler colonialism, Indigenous critical theory, and critical pedagogy. Recent revisions to the curriculum documents have responded to increasing calls for integration of content about First Nations, Métis, and Inuit peoples and Indigenous perspectives into education in BC. However, critical silences, problematic representations and placement of content, and subordination of Indigenous ways of knowing and being to settler-colonial epistemology and ontology hinder meaningful integration of Indigenous perspectives into the curriculum. In particular, the naturalization of settler-colonial sovereignty and territoriality in the curriculum reinstates settler interests and “commonsense.” This tendency is particularly problematic in the context of the contemporary neoliberalization of education in settler societies. This thesis proposes that decolonizing education in BC will require a shift in the ways settlers and Indigenous peoples relate in and with place. M.A.